Fast and automated detection of common carbapenemase genes using multiplex real-time PCR on the BD MAXTM system - Probst, Katja; Boutin, Sébastien; Bandilla, Michael; Heeg, Klaus; Dalpke, Alexander (Journal of microbiological methods, 2021)
Fast detection of carbapenemases in Gram-negative bacilli is necessary for accurate antibiotic treatment, prevention of further spreading and surveillance purposes. We analyzed the current occurrence of gene variants and designed two multiplex PCRs with hydrolysis probes. The assay was developed for the BD MAX™ system that combines DNA extraction and PCR in a fully automated procedure providing results within 3 h and was evaluated for detection of carbapenemases from bacterial isolates and directly from rectal swabs. The assay has a theoretic coverage of 97.1% for carbapenemases detected during the last years by the German National Reference Laboratory (NRL). A collection of 151 isolates from the NRL was used and all carbapenemase-positive bacteria (58/58) were identified correctly. The direct-PCR on rectal swabs revealed additional carbapenemase genes in 7 samples that were not identified by the culture-based method used as reference method. The assay allows detection of carbapenemases from clinical isolates and might also help in rapid detection directly from rectal samples.
Gesehen am 28.07.2021
Im Titel ist "TM" hochgestellt